2021
DOI: 10.1563/aaid-joi-d-19-00299
|View full text |Cite
|
Sign up to set email alerts
|

A CBCT Assessment of the Incidence and Location of the Lingual Foramen in the Anterior Mandible

Abstract: The purpose of this article is to assess the incidence of lingual foramina and associated vasculature in the anterior mandible to improve the understanding of their locations for dental implant placement. Intra-operative bleeding can be a significant complication. Pre-surgical assessment of the surgical site should be performed to identify anatomical landmarks. This can prevent a potential life-threatening haemorrhage that may compromise the airway.  Nutrient canals can occur in the anterior mandible and have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…We used fusion volumetric images in 26 Japanese subjects. The results of MLFs were consistent with other studies, with the number of MLFs distributed between 2 and 6, most predominantly below the incisors, followed by the premolars and finally the canines [ 10 , 11 , 13 , 29 ]. When we considered sex differences, we found similar findings to those of Yildirim [ 31 ] who state that women have slightly lower values in each of the variables analyzed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We used fusion volumetric images in 26 Japanese subjects. The results of MLFs were consistent with other studies, with the number of MLFs distributed between 2 and 6, most predominantly below the incisors, followed by the premolars and finally the canines [ 10 , 11 , 13 , 29 ]. When we considered sex differences, we found similar findings to those of Yildirim [ 31 ] who state that women have slightly lower values in each of the variables analyzed.…”
Section: Discussionsupporting
confidence: 91%
“…Some investigators supported that canals occur in the anterior mandible and had been reported to cause significant bleeding if violated [ 9 ]. The mandibular lingual foramens (MLFs) were the potential anatomical complication for dental implant placement in the anterior mandible [ 10 ]. They were described as the small foramina in the midline of the mandibular lingual region.…”
Section: Introductionmentioning
confidence: 99%
“…Splaying of the mandible after the bi-condylar fracture could be responsible for buccal impacted fracture with lingual obliquity. Though not many anatomical variations are found in the anterior mandible, the aetiology of oblique impacted fracture is unknown [ 11 , 12 ]. Yet, Pawar et al reported two cases of comminuted mandibular fractures caused by high-speed vehicle crashes [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that closed reduction can help prevent post-treatment nerve injury [ 14 ]. While anatomical variations in the course of the inferior alveolar nerve exist, there are no studies presenting these variations in IAN injuries [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%